Monograph of the genus elodea (hydrocharitaceae): part 2. the species found in the andes and western south america (1964)
The genus Elodea Richard in Michaux was first published in 1803(Fl. Bor.-Am. 1: 20, 1803), based upon the single species. E. Canadensis from Montreal, Quebec, Canada. Though this was stated to have perfect flowers, it is now certain that the holotype specimens and the plants in nature are dioecious. Very abundant are plants bearing pistillate flowers with three stigmas and three acicular staminodia. Staminate plants are rare, but occur throughout the natural range of the species. Their flowers have nine stamens, but no trace of a gynoecium. Two well known species are now separated and placed in the genus Egeria Planch., a group just monographed by the writer. Left in Elodeaare seventeen species. These are to be found in two broad areas, the northern ones in the United Statesand southern Canada; the southern ones in South America. As yet there is no evidence of any indigenous species of Elodea in Central America.